Digital Employee Experience (DEX): a preliminary study - Daud, Siti Rohana; Mukapit, Mukhiffun; Hussin, Norhusniyati; Yahya, Wan Kalthom; Abdul Rahim, Najihah (INSIGHT Journal, 2021)
In this article, we will present some preliminary findings on the digital employee experience (DEX), which is influenced by an organization’s digital transformation strategies. DEX evolved from employee experience (EX), but it has been modified to work in the digital world. Industrial Revolution 4.0 (IR 4.0) and digital transformation boost the organization awareness about positive DEX. This article also explored the success factors of DEX and its implication to organizations. Our discussion will be based on the Human Resource (HR) approach. We outline how organisations believe that their employees are the most valuable resource because they are considered internal customers and end-users who directly use technology and digital platforms that contribute to the organization’s profitability. Review of literature from previous academic research articles and practitioners’ opinion papers conducted as a methodology of this research. The factors studied will guide the organization on how to create great DEX.